Design and Implementation of Smart Home Security System based on GSM Technology - Supe, Aarti; Tajne, Kundan P; Bakade, Akshay; Mali, Nehal S; Kubal, Reema (International Journal of Computer Sciences and Engineering, 2025)
Home security has becoming an important issue nowadays. Home security is becoming necessary as the possibilities of thief are increasing day to day. Safety from theft are the most important issue of home security system for people. Smart home security system gives the signals in terms of calling ,SMS, Alarm. However, the GSM based smart home security systems provides intensify security as Whenever there is a motion in front of sensor or if thief try to open the door it directly call the owner or send the SMS In this there are two method for smart home security system. The first system uses calling And SMS system . Whenever there is a motion in front of sensor or if thief try to open the door it directly call the owner or send the SMS. The second method .The second system uses the camera. We can see through camera who is trying to enter the in house.